Cartografias do sombrio: arte, subjetividades e performances no universo gótico de Fortaleza - Ribeiro, Sandra Stephanie Holanda Ponte (2016)
In this dissertation, I accompany young trajectories tune with the Gothic in their leisure circuit in Fortaleza city, in order to observe how they lived an experience with this art world in different spaces and musical events. I bring to research the following questions: how these young people produce an experience with gothic from these meetings? What distinguishes or characterizes this experience? The work includes a description of the trajectories, events, performances, consumptions and affections that constitute and characterize these meetings, while seeking to describe the multiplicity of interactions and flows through the subjectivities of these young people. During the investigation, I use the concept of art world prepared by Becker (2010) as a methodological strategy into think of the gothic universe as a network of cooperation between individuals around artworks in the case, the Gothic art.